The Lower Cretaceous Chañarcillo and Neuquén Andean basins: ammonoid biostratigraphy and correlations - Aguirre-Urreta, Maria Beatriz; Mourgues, F. Amaro; Rawson, Peter F.; Bulot, Luc G.; Jaillard, Etienne (Geological Journal)
The Chañarcillo and Neuquén basins of the Central Andes shared a common geological history in the earlier part of the Early Cretaceous but from Barremian times onward their evolution began to diverge, probably due to an increasing activity of an intervening volcanic arc. The Berriasian to Lower Barremian sequences were mainly marine and include rich ammonoid faunas, with many taxa in common to both the basins. They include both Andean and near-pandemic forms, the latter providing some good correlation levels with the 'standard' Mediterranean sequence. Marine conditions persisted in the Chañarcillo Basin till Early Albian times; the associated ammonoid faunas include pandemic, Pacific and Antarctic genera. In contrast, in the Neuquén Basin evaporites and continental clastics of the Huitrín Formation mark the beginning of a long disconnection with the Pacific Ocean, though a short-lived marine incursion is represented by the carbonates of La Tosca Member of the Huitrín Formation. The ammonoid faunas of the two basins are compared here, and a detailed biostratigraphic division of the sequences is discussed and compared with the Mediterranean succession. Fil: Aguirre-Urreta, Maria Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Mourgues, Amaro F. Servicio Nacional de Geología y Minería; Chile Fil: Rawson, Peter F. University College London; Reino Unido Fil: Bulot, Luc G. Universite de Provence; Francia Fil: Jaillard, Etienne. IRD–LGCA, Maison des Géosciences; Francia